Critique of home constraint-induced movement therapy trial: constraint-induced movement therapy study prompts the need for further research - Boyd, Lara A.; Walker, Marion F. (American Heart Association, 2016)
Enhancing recovery from stroke with effective rehabilitation interventions remains an elusive goal.1 Although intensive rehabilitation therapies such as constraint-induced movement therapy (CIMT) show promise,2 the intervention has not been deployed in routine clinical practice. Slow uptake of CIMT in routine clinical practice has been attributed to its large demand on professional resources and patient compliance, as well as the costs associated with delivering high doses of therapy in a relatively short time. To remediate these limitations, there have been calls for modified versions of CIMT that are less intensive, lower cost, and easier to deliver.3 Recent work by Barzel et al4 attempted to advance the understanding of modified forms of CIMT by applying this therapy in the home setting. Home CIMT includes the basic elements of CIMT including repetitive training, transfer of activities, and constraint of the nonparetic hand. However, Home CIMT attempts to accomplish each of these goals within the individual’s home setting under the supervision of a nonprofessional coach.4 Although study participants were involved in overall goal setting for their therapeutic program, they only interacted with professional rehabilitation practitioners (Occupational or Physical Therapists) in 5 visits: 2 initial home visits to set up the program in the first week of a 4-week program and 3 additional sessions to adjust the program during the next 3 weeks. The overall goal was 40 hours of task practice with the paretic arm for a 20-day period.